Normal Flow Signal of the Pterygoid Plexus on 3T MRA in Patients without DAVF of the Cavernous Sinus - Watanabe, K.; Kakeda, S.; Watanabe, R.; Ohnari, N.; Korogi, Y. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Cavernous sinuses and draining dural sinuses or veins are often visualized on 3D TOF MRA images in patients with dural arteriovenous fistulas involving the CS. Flow signals may be seen in the jugular vein and dural sinuses at the skull base on MRA images in healthy participants, however, because of reverse flow. Our purpose was to investigate the prevalence of flow signals in the pterygoid plexus and CS on 3T MRA images in a cohort of participants without DAVFs. MATERIALS AND METHODS: Two radiologists evaluated the flow signals of the PP and CS on 3T MRA images obtained from 406 consecutive participants by using a 5-point scale. In addition, the findings on 3T MRA images were compared with those on digital subtraction angiography images in an additional 171 participants who underwent both examinations. RESULTS: The radiologists identified 110 participants (27.1%; 108 left, 10 right, 8 bilateral) with evidence of flow signals in the PP alone (n = 67) or in both the PP and CS (n = 43). Flow signals were significantly more common in the left PP than in the right PP. In 171 patients who underwent both MRA and DSA, the MRA images showed flow signals in the PP with or without CS in 60 patients; no DAVFs were identified on DSA in any of these patients. CONCLUSIONS: Flow signals are frequently seen in the left PP on 3T MRA images in healthy participants. This finding may be the result of flow reversal and should not be considered to indicate occult DAVF. CScavernous sinusDAVFdural arteriovenous fistulaEVemissary veinIPSinferior petrosal sinusPPpterygoid plexus